Light‐Driven Kinetic Resolution of α‐Functionalized Carboxylic Acids Enabled by an Engineered Fatty Acid Photodecarboxylase. Issue 25 (14th May 2019) - Xu, Jian; Hu, Yujing; Fan, Jiajie; Arkin, Mamatjan; Li, Danyang; Peng, Yongzhen; Xu, Weihua; Lin, Xianfu; Wu, Qi
Abstract: Chiral α‐functionalized carboxylic acids are valuable precursors for a variety of medicines and natural products. Herein, we described an engineered fatty acid photodecarboxylase ( Cv FAP)‐catalyzed kinetic resolution of α‐amino acids and α‐hydroxy acids, which provides the unreacted R ‐configured substrates with high yields and excellent stereoselectivity ( ee up to 99 %). This efficient light‐driven process requires neither NADPH recycling nor prior preparation of esters, which were required in previous biocatalytic approaches. The structure‐guided engineering strategy is based on the scanning of large amino acids at hotspots to narrow the substrate binding tunnel. To the best of our knowledge, this is the first example of asymmetric catalysis by an engineered Cv FAP. Abstract : Photoenzyme‐catalyzed kinetic resolution of α‐amino acids and α‐hydroxy acids was achieved for the first time by using engineered fatty acid photodecarboxylase ( Cv FAP) variants, which were generated through site‐specific mutagenesis based on large amino acid scanning. A series of R ‐configured α‐functionalized carboxylic acids were obtained with ee values up to 99 % and excellent stereoselectivity.